PENGARUH PENGELUARAN PEMERINTAH SEKTOR KESEHATAN DAN PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM): (Studi Pada Pemerintah Provinsi di Indonesia Tahun 2017-2021) - Damayanti, Atika Putri; Suryaningrum, Diah Hari (Politeknik Negeri Ambon, 2023)
This study aims to test and analyze the effect of government expenditure on the health and education sectors on HDI. This research uses a quantitative approach. The population of this research was provincial governments in Indonesia in 2017-2021, and purposive sampling was used to select the research sample. The research sample amounted to 31 with a period of 5 years, which means the total amount of data is 155. The data analysis technique uses panel data regression analysis assisted by the Eviews application. The findings of this study are that government expenditure on the health sector does not affect HDI. In contrast, government expenditure on education affects HDI and its components, namely life expectancy, education, and per capita expenditure. This study implies that the management of health and education funds needs to be optimized to improve human development. The government needs to think carefully about how to use these funds effectively and on target. A well-targeted budget allocation will support the achievement of increased human development.